Free radicals and antioxidants status in neonates with congenital malformation - Bedabrata Mukhopadhyay; Ajay Narayan Gongopadhyay; Anjali Rani; Roshni Gavel; Surendra Pratap Mishra (Wolters Kluwer Medknow Publications, 2015)
Background: Several studies using animal models have shown that oxidative stress during pregnancy may play an important role in causing birth defects. Congenital anomalies affect an estimated 270,000 newborns who die during the first 28 days of life every year from different birth defects. Hence, at present many research works are going on to reduce the infant mortality from congenital anomaly. [1] Objective: The objective was to measure the oxidant and antioxidant level in the serum of newborn babies with the congenital anomaly and compare these levels with age and sex matched normal neonates. This is to identify any role of oxidative stress in the causation of congenital anomaly. Materials and Methods: This case-control study included 159 participants: 106 newborns with the congenital anomaly and 53 healthy newborns. The markers of oxidative stress like serum malondialdehyde (MDA) level, protein carbonyl (PC) level, and the activity of antioxidants such as Vitamin C, glutathione were measured in both cases (neonates with congenital anomaly) and controls (normal healthy neonates). These parameters were statistically compared. Results: MDA levels and PC levels were significantly higher (P < 0.0001), and Vitamin C and reduced glutathione levels were significantly lower (P < 0.0001), in newborns with congenital malformation than in healthy newborns. Conclusions: Increased lipid peroxidation and protein carbonylation might play an important role in the pathogenesis of congenital anomaly. Impairment of the free radical/antioxidant balance is leading to increased free radical damage in neonates with congenital malformation.